Inclusive Islamic Religious Education for Multicultural Elementary School Contexts - Abdulloh, Ilyas; Nurdiyansah , Riyan; Juwita , Reni; Selamet , Selamet (Universitas Muhammadiyah Sidoarjo, 2026)
In a diverse and increasingly globalized education system, inclusive and multicultural Islamic education is becoming increasingly important. This study aims to explore the development of an inclusive Islamic Religious Education (IRE) learning model for students from diverse religious and cultural backgrounds. The purpose of the study is to identify and evaluate the application of multicultural approaches in Islamic education to foster tolerance, respect for diversity, and social harmony. The research method employed is a literature review, which examines various scholarly sources on inclusive and multicultural education, focusing on the integration of cultural diversity within the Islamic education curriculum. The study found that current models often fail to address the diverse needs of students, particularly at the elementary school level, where students' character development is crucial. Additionally, while multicultural education has been emphasized in higher education, its application in elementary schools remains underexplored. The research suggests that Islamic education, when designed to include multicultural principles, can significantly contribute to building a tolerant and inclusive society by fostering mutual respect among students of different backgrounds. The study concludes that the development of a more inclusive Islamic education model is essential, as it can help create a learning environment that supports cultural diversity and encourages peaceful coexistence. Further research is necessary to address the challenges in implementing these educational strategies in diverse classrooms, and to provide practical guidelines for educators and policymakers to foster inclusivity in Islamic education. Highlights: Multicultural integration within Islamic Religious Education supports tolerant social attitudes among students. Elementary-level implementation faces structural constraints related to pedagogy and educator preparation. Curriculum alignment with cultural and religious diversity remains limited in current educational practice. Keywords: Tolerance, Multicultural, Cultural Diversity, Inclusive Islamic Religious Education